Activation of the Cannabinoid Receptor Type 1 Decreases Glutamatergic and GABAergic Synaptic Transmission in the Lateral Amygdala of the Mouse - Azad, Shahnaz Christina (Cold Spring Harbor Laboratory Press, 2003)
The endogenous cannabinoid system has been shown recently to play a crucial role in the extinction of aversive memories. As the amygdala is presumably involved in this process, we investigated the effects of the cannabinoid receptor agonist WIN 55,212-2 (WIN-2) on synaptic transmission in the lateral amygdala (LA) of wild-type and cannabinoid receptor type 1 (CB1)-deficient mice. Extracellular field potential recordings and patch-clamp experiments were performed in an in vitro slice preparation. We found that WIN-2 reduces basal synaptic transmission and pharmacologically isolated AMPA receptor- and GABA(A) receptor-mediated postsynaptic currents in wild-type, but not in CB1-deficient mice. These results indicate that, in the LA, cannabinoids modulate both excitatory and inhibitory synaptic transmission via CB1. WIN-2-induced changes of paired-pulse ratio and of spontaneous and miniature postsynaptic currents suggest a presynaptic site of action. Inhibition of G(i/o) proteins and blockade of voltage-dependent and G protein-gated inwardly rectifying K(+) channels inhibited WIN-2 action on basal synaptic transmission. In contrast, modulation of the adenylyl cyclase-protein kinase A pathway, and blockade of presynaptic N- and P/Q- or of postsynaptic L- and R/T-type voltage-gated Ca(2+) channels did not affect WIN-2 effects. Our results indicate that the mechanisms underlying cannabinoid action in the LA partly resemble those observed in the nucleus accumbens and differ from those described for the hippocampus.